SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) AND LAVENDER AROMATHERAPY REDUCES MATERNAL ANXIETY - Susanti Susanti; Fitria Hikmatul Ulya; Dyah Ayu Wulandari; Mei Lia Zulis Windiarti (Jurnal Smart Kebidanan, 2026)
Anxiety during the third trimester of pregnancy is a common issue that can negatively impact both maternal and fetal health. Non-pharmacological interventions such as the Spiritual Emotional Freedom Technique (SEFT) and lavender aromatherapy have been shown to effectively reduce anxiety levels. Preliminary data at Limpung indicated that approximately 30% of third trimester pregnant women experienced moderate to severe anxiety.Objective: To determine the effect of SEFT and lavender aromatherapy combination on anxiety levels in third trimester pregnant women.Method: This study used a pre-experimental design with a one group pretest-posttest approach. The sampling technique used purposive sampling, with a sample size of 22 respondents. The instrument used was the PRAQ-R2 questionnaire. Data were analyzed using the Wilcoxon test.Results: There was a significant decrease in anxiety levels before and after the intervention with a ƿ-value obtained was less than 0.05. The average anxiety level decreased from moderate to mild.Conclusion: The combination of SEFT and lavender aromatherapy is effective in reducing maternal anxiety levels among third-trimester in the Limpung area.